Os critérios de decisão MAP e ML: Resumindo e concluindo... - Sílvio Almeida Abrantes Abrantes (2009)
In this text two approaches to signal estimation are presented: the Maximum a Posteriori Probability (MAP) and the Maximum Likelihood (ML) estimation methods.